2021
DOI: 10.1186/s12951-020-00747-7
|View full text |Cite
|
Sign up to set email alerts
|

Density of surface charge is a more predictive factor of the toxicity of cationic carbon nanoparticles than zeta potential

Abstract: Background A positive surface charge has been largely associated with nanoparticle (NP) toxicity. However, by screening a carbon NP library in macrophages, we found that a cationic charge does not systematically translate into toxicity. To get deeper insight into this, we carried out a comprehensive study on 5 cationic carbon NPs (NP2 to NP6) exhibiting a similar zeta (ζ) potential value (from + 20.6 to + 26.9 mV) but displaying an increasing surface charge density (electrokinetic charge, Qek f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 69 publications
12
70
0
Order By: Relevance
“…In the literature, a greater toxicity of positive CDs compared to negative ones was reported [38,49,50]. However, our group also recently demonstrated that a positive zeta potential for NPs does not necessarily translate into toxicity, and that the surface charge density of NPs influences their toxicity as well [39], which is confirmed in this present study. Regarding the cellular models, the viability loss induced by CD-PEI600 and CD-PEHA was greater in THP-1 than in A549 mono-cultures.…”
Section: Cytotoxicity Of Cds and Cell Death Mechanisms In Mono-and Co-culturessupporting
confidence: 88%
See 3 more Smart Citations
“…In the literature, a greater toxicity of positive CDs compared to negative ones was reported [38,49,50]. However, our group also recently demonstrated that a positive zeta potential for NPs does not necessarily translate into toxicity, and that the surface charge density of NPs influences their toxicity as well [39], which is confirmed in this present study. Regarding the cellular models, the viability loss induced by CD-PEI600 and CD-PEHA was greater in THP-1 than in A549 mono-cultures.…”
Section: Cytotoxicity Of Cds and Cell Death Mechanisms In Mono-and Co-culturessupporting
confidence: 88%
“…Applied to our safety study on cationic CDs with increasing charge density, this is particularly relevant since only the co-culture model allowed us to find that CDs of medium (CD-PEHA) and low (CD-DMEDA) positive surface charge density could induce a pro-inflammatory response, with a greater effect for CD-PEHA compared to CD-DMEDA. If our previous work had already showed an inflammatory effect for cationic CDs with a high positive charge density [39], we report here for the firsttime a pro-inflammatory potential for cationic CDs of lower charge density. By using the co-culture model developed in this work, we also showed that the inflammatory response induced by cationic CD is hierarchically related to the surface charge density of these NPs.…”
Section: Oxidative Stress and Inflammatory Response Evoked By Cds In The Mono-and Co-culture Modelssupporting
confidence: 55%
See 2 more Smart Citations
“…Therefore, taking all these factors together, 0.01% (w/v) HMWC was chosen as the coating agent for PS80 PBCA NP. The effect of chitosan-coating on the cytotoxicity of the PS80 PBCA NP is intriguing, although cationic nanoparticles are known to elicit membrane-permeabilizing effects that can irreversibly lead to cell damage and death [44], the exact structural conformation on the distribution of electric charge in the presence of PS80 PBCA NP, and together with the modification of electric charge by the interacting medium components as the protein corona evolves, may exert a stronger influence on its final cytotoxicity profile [45,46]. Additional factors other than electric charge can augment the cellular responses to nanoparticles, for example, the cytotoxicity of nanoparticles charge-modified by coating with chitosan has been shown to be dependent on the core material and stability of the coated nanoparticle, and the cell type and growth characteristics rather than the electric charge of chitosan alone [47,48].…”
Section: Discussionmentioning
confidence: 99%